Financial Literacy, Financial Technology Literacy, and Capital Market Participation - Nugroho Sasikirono; Harlina Meidiaswati; Nur Maulydia Rachman; Muhammad Madyan (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2023)
Objective: This study aims to determine the effect of financial literacy and fintech literacy on capital market participation. It also examines the effects of individual characteristics (i.e., gender, age, student's allowances and income, parent's education, and parent's income) on financial and fintech literacy. Design/Methods/Approach: This study obtained 349 data from email and field surveys using purposive sampling. Data analysis was performed using OLS and path analysis. Findings: Results show that the level of student financial literacy is sufficiently literate, with a moderate level of fintech literacy but low capital market participation. The results also show financial and fintech literacy positively affects capital market participation. Financial literacy also exhibits indirect effects on capital market participation. Analysis of the determinants of literacy shows that gender, age, student allowances, and income have a significant positive effect on financial literacy and fintech literacy. We also find that parental education and income show a negative effect on fintech literacy. Originality/Value: This study is the first to examine the relationship between financial literacy, fintech literacy, and capital market participation in young adults in metropolitan cities in Indonesia. The results are expected to provide insight for the authorities of the monetary system and the capital market to develop strategies for the more intense involvement of young adults in the capital market. Practical/Policy implication: This study highlights the importance of educating students about financial and fintech literacy to increase their participation in the capital market. Decision-makers should focus on providing intense education on portfolio investment, risk and return, and investment instruments. Financial authorities should also collaborate with fintech operators and securities companies to promote capital market products through fintech and educate the public with more comprehensive information.